Analyzing the Antecedents and Consequences of Teacher Job Satisfaction in the Digital 4.0 Era - Romy, Elly; Pada, Andi Tenri; Susanti, Neneng; Umiyati, Hesti; Sudirman, Acai (FKIP Universitas Lampung, 2022)
Analyzing the Antecedents and Consequences of Teacher Job Satisfaction in the Digital 4.0 Era. Objectives: This research analyzes the antecedents and consequences of teacher job satisfaction in the digital 4.0 era. Methods: This study uses a quantitative approach with a theoretical model assessed by PLS-SEM analysis. The sampling technique was oriented to purposive sampling, so the samples obtained were 125 teachers. Findings: The results of this research suggest that principal supervision has no significant effect on teacher job satisfaction, while compensation significantly affects teacher job satisfaction. The results of this research also confirm that teacher job satisfaction significantly affects organizational citizenship behavior and teacher performance. Conclusion: This study concludes that the principal supervision program must be realized in implementing clinical and non-clinical supervision programs. Giving fair compensation will give teachers their motivation to work optimally. Job satisfaction shown by teachers can directly improve organizational citizenship behavior and teacher performance.Keywords: principal supervision,compensation,teacher job satisfaction, organizational citizenship behavior, teacher performance.DOI: http://dx.doi.org/10.23960/jpp.v12.i3.202222